Exploring Cerebrospinal Fluid: Validation of a New Method for Quantification of 39 Drugs of Abuse by LC-MS/MS - Alexandra Dimitrova; Emma Beatrice Croce; Gaia Iaquinta; Elisa Ferri; Simone Faccioli; Giulia Chiavacci; Barbara Gualco; Martina Focardi; Simone Grassi; Fabio Vaiano (Forensic Sciences)
The use of cerebrospinal fluid (CSF) in post-mortem (PM) toxicological analysis is an under-addressed topic, likely due to the technical complexity of the collection of a proper sample. However, it is a matrix of significant interest since it has similar chemical and physical properties to the blood and it is less exposed to risks like PM redistribution and diffusion due to its anatomical location. This study aimed to validate a sensitive analytical method for the quantification of drugs of abuse and their metabolites (i.e., cocaine, ketamine, amphetamine, MDPV, 6-monoacetylmorphine, morphine, codeine, and methadone) through liquid chromatography–tandem mass spectrometry (LC-MS/MS). CSF was collected through ventricular puncture, and 200 µL was deproteinated with acetonitrile (600 µL). Quantification was carried out, acquiring two MRM transitions for each compound in positive ionization mode. Chromatographic separation was achieved with a C18 column. Limits of quantification ranged from 0.05 to 5 ng/mL. Bias and precision were always within the acceptance criteria. Ion enhancement and suppression effects were observed depending on the substance. The method validated here was applied to a real case, proving to be suitable for PM analysis. CSF and blood were positive for methadone (460 vs. 280 ng/mL), cocaine (125 vs. 69 ng/mL), benzoylecgonine (4640 vs. 3160 ng/mL), and lorazepam (19 vs. 25 ng/mL). In the future, this will be useful for the evaluation of CSF as a valuable alternative matrix in PM investigations.